Evaluating the Test Validity of the Comprehensive Assessment of Psychopathic Personality Symptom Rating Sale (CAPP SRS). Issue 6 (24th October 2022) - Cooke, David J.; Hart, Stephen D.; Logan, Caroline; Michie, Christine
Abstract: The Comprehensive Assessment of Psychopathic Personality Symptom Rating Scale (CAPP SRS) is a relatively new measure of psychopathic personality disorder (PPD) based on the CAPP concept map of psychopathy. To investigate the CAPP SRS, we identified the most plausible formal test structure for the test using the framework proposed by Slaney and Maraun, identified an appropriate quantitative characterization of that test structure, and then statistically evaluated it based on analysis of CAPP SRS data collected from a multisite sample of 314 adult male correctional offenders and secure hospital patients in Scotland and England. Overall, the CAPP SRS survived falsification when observed test data were compared to expectations based on the unidimensional monotone latent variable or UMLV model of Holland and Rosenbaum. CAPP SRS composite scores calculated consistent with the UMLV model had good measurement precision and good external validity with respect to scores on an established test of PPD. The findings provide provisional support for the test validity of the CAPP SRS and highlight the importance of theory-driven evaluations of test validity.